Validitas Modul Sistem Koloid Berbasis Inkuiri Terbimbing - Agnouri Rahmayati; Iryani Iryani (Universitas Negeri Padang, 2019)
The Curriculum 2013 requires teacher to carry out teaching-learning process using the scientific approach, so that it can encourage students to be more active individually or in groups. The Colloid system is a chemical material that is studied in the XI class of high school even semester. This study aims to produce a colloidal system module guided inquiry-based equipped with HOTS questions, and to develop a valid module. The type of research used is Research and Development (R and D). The development model used is the Plomp development model which consists of 3 stages that are preliminary research, prototype stage and assesment. The instrument of data collection used is the instrument of validity. The research data was analyzed using the Cohen Kappa formula. The module was validated by 5 validators.The results of the questionnaire analysis of validity by the validator were 0.90 with a very high validity category.